2016
DOI: 10.3389/fpsyg.2016.00783
|View full text |Cite
|
Sign up to set email alerts
|

Fine Motor Skills Predict Maths Ability Better than They Predict Reading Ability in the Early Primary School Years

Abstract: Fine motor skills have long been recognized as an important foundation for development in other domains. However, more precise insights into the role of fine motor skills, and their relationships to other skills in mediating early educational achievements, are needed to support the development of optimal educational interventions. We explored concurrent relationships between two components of fine motor skills, Fine Motor Precision and Fine Motor Integration, and early reading and maths development in two stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 88 publications
(130 reference statements)
9
104
2
8
Order By: Relevance
“…In studies analysing correlations between fine motor integration and mathematics performance, six studies [48,52,55,57,58,63] reported significant very weak to weak associations (r = 0.16−0.38), seven studies [49,53,56,58,60,64,71] reported moderate associations (r = 0.417−0.59), and two studies [56,64] reported a strong association (r = 0.612−0.673). The one study [45] that did not report a significant association between fine motor integration and mathematics performance was the only study conducted with high school participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies analysing correlations between fine motor integration and mathematics performance, six studies [48,52,55,57,58,63] reported significant very weak to weak associations (r = 0.16−0.38), seven studies [49,53,56,58,60,64,71] reported moderate associations (r = 0.417−0.59), and two studies [56,64] reported a strong association (r = 0.612−0.673). The one study [45] that did not report a significant association between fine motor integration and mathematics performance was the only study conducted with high school participants.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to the strength of correlations between variables reported, 10 studies [48,52,53,55,58,63,81,83,85,87] found very weak to weak correlations (r = 0.163–0.38), six studies [39,58,59,71,81,88] found moderate associations (r = 0.40–0.47), and two studies [60,71] reported a strong correlation (r = 0.60–0.62). A total of 11 [48,52,54,55,58,60,69,81,83,85,86] of the 17 studies reporting significant associations had fair-to-good methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…These cognitive and motor measures were chosen because of their close association with the development of fundamental scholastic skills, such as mathematics and literacy (e.g., Nunes et al, 2007; Berg, 2008; Mulder et al, 2010; Westerndorp et al, 2011; Bourke et al, 2014; Simms et al, 2014; Pitchford et al, 2016). Accordingly, a measure of scholastic skill - mathematics - that is taught from the start of formal schooling in both Malawi and the UK was also included to cross-validate the new assessment tool.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the influence of early VMI for later academic achievement has been empirically supported (Becker, Miao, Duncan, & McClelland, 2014;Cameron et al, 2012Cameron et al, , 2015Carlson, Rowe, & Curby, 2013;Grissmer, Grimm, Aiyer, Murrah, & Steele, 2010). Studies considering VMI and non-motor spatial skills concurrently report that both constructs are associated with and/or are predictive of better performance in mathematics (Carlson et al, 2013;Pieters et al, 2012;Pitchford et al, 2016;Sortor & Kulp, 2003).…”
Section: Link Between Spatial Skills and Early Mathematicsmentioning
confidence: 99%
“…Classically, tasks of spatial perception, mental rotation and spatial visualization, require the treatment of visual information, while tasks of VMI involve the coordination between the treatment of visual input and motor output (Cameron et al, 2015). Empirical research on the relation between mathematics and spatial skills suggests considering VMI when studying this relationship in young children (Carlson, Rowe, & Curby, 2013;Pieters, Desoete, Roeyers, Vanderswalmen, & Van Waelvelde, 2012;Pitchford, Papini, Outhwaite, & Gulliford, 2016;Sortor & Kulp, 2003). In the following, VMI will be considered as an aspect of spatial skills (in line with Frostig, Lefever, & Whittlesey, 1961 …”
Section: Definition and Terminologymentioning
confidence: 99%